Review on the air temperature and humidity produce by solar dryer and potential to be reused - Misha, Suhaimi; Hashem Salem Almshwali, Eslam Ahmed; Mohd Rosli, Mohd Afzanizam; Haminudin, Nor Faizah; Mohd Sa'at, Fatimah Al-Zahrah; Abdul Munir, Fudhail; Ali Al-Abidi, Abduljalil (Penerbit Akademia Baru, 2025)
This article presents a comprehensive review of recent advancements in the reuse of waste heat from solar food dryers, a strategy that holds significant potential to improve system efficiency and sustainability. Solar drying systems typically discharge air at temperatures between 40°C and 70°C, resulting in a substantial loss of free solar thermal energy up to 50% of total energy. This review introduces novel approaches to capturing and reusing this low-quality heat, including the integration of desiccant materials that can boost drying efficiency by up to 64%, and innovative designs like rotating dryer wheels, which increase effective heat gains by an average of 153%. Unlike previous studies, this article not only aggregates and analyzes field test data such as outlet temperatures, humidity levels, and heat recovery efficiencies but also identifies practical and scalable solutions for heat reuse, such as water heating, space heating, and heating nearby cold rooms. By providing quantitative results and exploring the potential for continuous 24-hour operation through advanced heat management techniques, this review offers new insights and practical guidelines for engineers and researchers aiming to make solar drying processes more energy-efficient and commercially viable. This work is particularly relevant for those interested in developing sustainable agricultural practices, as it highlights the most promising methods for reducing energy waste and enhancing the overall performance of solar dryers. The novel synthesis of existing technologies and the identification of key areas for future research make this article a valuable resource for advancing the field of solar drying.